A community based investigation of urban male partners’ understanding and participation in maternity care: A cross-sectional study in Bangladesh - Quazi Maksudur Rahman; Md. Tajuddin Sikder (PLoS ONE, 2026)
Background Male partners’ adequate understanding and engagement in maternity care plays a crucial role in enhancing women’s reproductive health. However, male involvement in maternal and child health care is still significantly below expectations, even though they perform key roles. Low knowledge levels appear to be a significant barrier to effective involvement. Objective To examine the urban married men’s understanding and involvement in maternity care, as well as the factors associated with it. Methods In this quantitative study, 422 data were collected through a structured questionnaire via face-to-face interviews between July and September 2022 among urban married males living in Dhaka City. The socio-demographic characteristics, level of understanding, males’ attitude and involvement status regarding maternity care were measured. The descriptive statistics along with logistic regression analysis were performed using STATA version 14.1. Results A total of 422 urban married male were considered for this study, and the mean age of the study participants was 37.21 (SD ± 8.79). About 55.92% of the male participants had good understanding and 54% had positive attitude towards maternity care. Around 47% had good involvement in maternity care. Male who had good involvement in maternity care were more likely to have good understanding (AOR: 1.73; CI: 1.13 to 2.64; p = 0.01). In addition, urban male who had government jobs (AOR: 6.48; CI: 1.54 to 27.22; p = 0.01), positive attitude (AOR: 1.79; CI: 1.16 to 2.76; p = 0.01) and good understanding (AOR: 1.74; CI: 1.14 to 2.66; p = 0.01) were more likely to get involved in maternity care. Conclusion Maternity care was well-understood and positively viewed by the most urban married males, but their level of involvement was far below the expected level. However, to strengthen safe motherhood initiatives in Bangladesh, it is important to properly address the understanding and participation of urban males in maternity care and other related factors.